2001
DOI: 10.1002/ajpa.1046
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of probable scurvy in subadults from archeological sites in North America

Abstract: The authors surveyed subadult human skeletons from Native American archeological sites in the United States for evidence of skeletal lesions associated with scurvy. Geographic regions surveyed include the Midatlantic area, the Southeast (Florida), the Southwest, and the Plains. The prevalence of probable subadult scurvy ranged from zero in the Plains samples to 38% in a small sample from Florida. These data indicate the likelihood that scurvy was a significant childhood disease in many Native American groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
172
0
20

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 173 publications
(203 citation statements)
references
References 6 publications
10
172
0
20
Order By: Relevance
“…Using both anatomical (Ortner & Ericksen, 1997) and archaeological samples of non‐adult remains (Ortner et al, 1999, 2001) these authors have identified a suite of macroscopic bony lesions which they argue can be intuitively linked to the hemorrhagic effects of scurvy, specifically low‐grade bleeding due to the effects of minor muscular actions—such as masticatory movements—on weakened vasculature. The scorbutic lesions proposed by Ortner et al, as well with their anatomical associations and hypothesized mechanisms of formation, are outlined in Table 1 and described in detail in section ten.…”
Section: The “Ortner Criteria”: Paleopathological Inference Using Knomentioning
confidence: 99%
See 4 more Smart Citations
“…Using both anatomical (Ortner & Ericksen, 1997) and archaeological samples of non‐adult remains (Ortner et al, 1999, 2001) these authors have identified a suite of macroscopic bony lesions which they argue can be intuitively linked to the hemorrhagic effects of scurvy, specifically low‐grade bleeding due to the effects of minor muscular actions—such as masticatory movements—on weakened vasculature. The scorbutic lesions proposed by Ortner et al, as well with their anatomical associations and hypothesized mechanisms of formation, are outlined in Table 1 and described in detail in section ten.…”
Section: The “Ortner Criteria”: Paleopathological Inference Using Knomentioning
confidence: 99%
“…The scorbutic lesions proposed by Ortner et al, as well with their anatomical associations and hypothesized mechanisms of formation, are outlined in Table 1 and described in detail in section ten. The majority of these are cranial, consisting of clustered, fine cortical porosity and are argued to be the result of bleeding of vasculature associated with the muscles of mastication, such as the temporalis and pterygoids (Ortner et al, 1999, 2001; Ortner & Ericksen, 1997). Capillary proliferation is part of the inflammatory response to the presence of extravascular blood; these new vessels act as a delivery system for phagocytic cells of the innate immune system to aid in the removal of hemorrhagic material (Browder, Folkman, & Pirie‐Shepherd, 2000).…”
Section: The “Ortner Criteria”: Paleopathological Inference Using Knomentioning
confidence: 99%
See 3 more Smart Citations